Current Concepts of Antigen Cross-Presentation - Embgenbroich, Maria; Burgdorf, Sven (Frontiers in Immunology, 2018)
Dendritic cells have the capacity to efficiently present internalized antigens on MHC I molecules. This process is termed cross-presentation and plays an important role in the generation of an immune response against viruses and tumors, after vaccinations, or in the induction of immune tolerance. The molecular mechanisms enabling cross-presentation have been topic of intense debate since many years. However, a clear view on these mechanisms remains difficult, partially due to important remaining questions, controversial results and discussions. Here, we give an overview of the current concepts of antigen cross-presentation and focus on a description of the major cross-presentation pathways, the role of retarded antigen degradation for efficient cross-presentation, the dislocation of antigens from endosomal compartment into the cytosol, the reverse transport of proteasome-derived peptides for loading on MHC I and the transport of the cross-presentation machinery from the ER to endosomes. We try to highlight recent advances, discuss some of the controversial data and point out some of the major open questions in the field.